Segmentasi Citra MRI dengan Menggunakan Metode BLOB - Ahmad Houlan Dalimunthe (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2020)
Image processing is a process to produce images according to your wishes or the quality is better. The input is an image and the output is also an image but with better quality than the input image. Digital image processing is a process that aims to manipulate and analyze images with the help of computers. This is done to obtain alternative solutions to a problem with more efficient results and good accuracy, for example for the detection of osteoporosis from X-ray images and for video compression. Image (image) is another term for images as a form of visual information that plays an important role in the multimedia component. Along with technological developments in the field of computerization, image processing technology has been widely used in various fields including medicine and the entertainment industry. The segmentation process in a digital image that separates an object from the background or background is obtained from the RGB value in each pixel in the digital image so that the object can be processed for other purposes. Along with the development of technology in applications that process digital images, the segmentation process becomes increasingly necessary. The results of the segmentation must also be more accurate because if the results of the segmentation are inaccurate it will affect the results of the next process. In general, the segmentation process is divided into three parts based on classification, by edge and by area.